2006
DOI: 10.1097/01.qai.0000224975.45091.a5
|View full text |Cite
|
Sign up to set email alerts
|

Range of Normal Neutrophil Counts in Healthy Zimbabwean Infants

Abstract: Mother-to-child HIV prevention trials in sub-Saharan Africa use the US National Institutes of Health Division of AIDS (DAIDS) grading scale to monitor hematologic toxicity. A recent study of nevirapine prophylaxis given for 6 months in breast-feeding Zimbabwean infants reported several cases of relative neutropenia in clinically well infants, raising concerns of drug toxicity. However, the DAIDS tables are based on normal blood counts for white infants, although there is evidence that black African infants may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…[31][33] However, the findings of this study indicate that an absolute increase in severe neutropenia related to cotrimoxazole is likely to be at most 5%. In settings where either continued breastfeeding or limited access to early infant HIV diagnosis make the use of cotrimoxazole prophylaxis a consideration, these negative findings are important to inform decisions about the optimal period for prophylaxis.…”
Section: Discussionmentioning
confidence: 66%
“…[31][33] However, the findings of this study indicate that an absolute increase in severe neutropenia related to cotrimoxazole is likely to be at most 5%. In settings where either continued breastfeeding or limited access to early infant HIV diagnosis make the use of cotrimoxazole prophylaxis a consideration, these negative findings are important to inform decisions about the optimal period for prophylaxis.…”
Section: Discussionmentioning
confidence: 66%
“…Few data exist regarding the implications of medication-induced neutropenia for child health outcomes in Africa, and normal neutrophil count ranges for African infants may be lower than ranges in the populations used in the development of the DAIDS toxicity tables. 4043 Lastly, we detected an increase in CTX resistance among commensal E. coli stool isolates in the CTX arm; the clinical consequences of this finding are unknown.…”
Section: Discussionmentioning
confidence: 78%
“…8,13,16,17,18 These studies have also observed significant differences with values from developed countries, in haematologic parameters such as haemoglobin and absolute neutrophil, which are normally used for toxicity grading in clinical trials, and consequently have implications in patient management and the conduct of clinical trials. 18,19,20,21 A significant number of potential African volunteers are excluded from participating in vaccine trials because screening, enrollment and follow-up monitoring is mostly based on values derived from predominantly White populations. A study in Uganda 19 documented an exclusion rate of as high as 69% of vaccine clinical trial participants because of haematologic abnormalities, 83% of whom could have been included in the studies if local reference ranges were used.…”
Section: Introductionmentioning
confidence: 99%